SISTEM INFORMASI PENJUALAN ONLINE PADA PT. SR12 HERBAL PERKASA DISTRIBUTOR UTAMA BEKASI - Rani Herdiyanti (LPPM Universitas Abdurrab, 2023)
SR12 Herbal Perkasa Main Distributor Bekasi is a business engaged in the field of beauty. Having an average turnover of 120 million per month, the management of online sales which are operated through Microsoft Excel is not optimal so that several obstacles are found in the running business processes. For example, forgetting to record customer orders, late processing orders via Whatsapp, typing in wrong addresses and goods which result in wrong shipments. Thus, it’s necessary to have an information system to assist the running of business processes within the company. The research method used is SDLC. The author uses the PHP programming language, Bootstrap framework, MySQL database server, and Sublime text editor software. This information system can facilitate the process of online sales transactions because customers can access and make purchases in real time, reports are generated more accurately so that sales records become more organized, effective and efficient.